Structure-Function Relationships of the Non-Lanthionine-Containing Peptide (class II) Bacteriocins Produced by Gram-Positive Bacteria - Nissen-Meyer, J.; Rogne, P.; Oppegard, C.; Haugen, H. S.; Kristiansen, P. E. (Current Pharmaceutical Biotechnology, 2009)
This review focuses on the structure and mode-of-action of non-lanthionine-containing peptide bacteriocins produced by Gram-positive bacteria. These bacteriocins may be divided into four groups: (i) the anti-listerial one-peptide pediocin-like bacteriocins that have very similar amino acid sequences, (ii) the two-peptide bacteriocins that consist of two different peptides, (iii) the cyclic bacteriocins, and (iv) the linear non-pediocin-like onepeptide bacteriocins. These bacteriocins are largely cationic, contain 20 to 70 residues, and kill cells through membrane- permeabilization. The pediocin-like bacteriocins are the ones that are best characterized. Upon contact with target membranes, their cationic N-terminal half forms a β-sheet-like structure that binds to the target cell surface, while their more hydrophobic helical-containing C-terminal half penetrates into the hydrophobic core of target-cell membranes and apparently binds to the mannose phosphotransferase permease in a manner that results in membrane leakage. Immunity proteins that protect cells from being killed by pediocin-like bacteriocins bind to the bacteriocin- permease complex and prevent bacteriocin-induced membrane-leakage. Recent structural analyses of two-peptide bacteriocins indicate that they form a helix-helix structure that penetrates into cell membranes. Also these bacteriocins may act by binding to integrated membrane proteins. It is proposed that many membrane-active peptide bacteriocins kill target-cells through basically the same mechanism; the common theme being that a membranepenetrating part of bacteriocins bind to a membrane embedded region of an integrated membrane protein, thereby causing conformational alterations in the protein that in turn lead to membrane-leakage and cell death.
Keywords: cyclic bacteriocins